Glutathione S-Transferase Activity in Tissues of Rats Exposed to Fenarimol - Ozcelebi,Halime (2021)
Abstract The unconscious use of pesticides causes various adverse effects on non-target organisms, including humans. Enzymes that control metabolism become the target of the pesticide and the organs are damaged due to toxic effects. Glutathione s-transferase (GST, EC 2.5.1.18), an important enzyme of the detoxification mechanism and antioxidant defense system, can be affected by such toxic substances. Therefore, the effect of fenarimol on GST enzyme activity was investigated in our study. For this, 200 mg/kg fenarimol was administered intraperitoneally to male and female rats at different periods (2, 4, 8, 16, 32, 64 and 72 hours). After application, GST enzyme activity was analysed in the liver, kidney, brain and small intestine tissues of the rats. According to our results, activation (liver, kidney, small intestine) or inhibition (brain) of the generally GST enzyme was observed in the tissues of rats exposed to fenarimol. It is thought that the increase and/or decrease in this enzyme activity may be the cause of the toxic effect of fenarimol.